BERTUMBUH DALAM RELASI DENGAN KRISTUS BERDASARKAN KOLOSE 2:6-7 - Sion Saputra; Hana Suparti; Talizaro Tafonao (Jurnal Shanan, 2020)
In this article, the author made a study of growing in a relationship with Christ according to Colossians 2:6-7. This article began from the author's concern about the shallow condition of Christian faith at this time, wich can easily be sucked in by the false teachings that are increasingly prevalent in social media. The rapid development of science and technology allows believers to obtain various teachings that have existed ind social media that are not in accordance with the word of God. The purpose of this article is to present the results of study on how believers grow in their relationship with Christ. This article analyzes growing in a relationship with Christ according to Colossians 2:6-7, so that Paul's counsel to the Colossians can also be carried out by the church today. The method used by the author in this article is a qualitative research method with a ecegetical approach. The analysis process carried out by the author was exeggesis the biblical text and analyze reliable secondary sources to produce accountable studies. The results of this study found that to be able to grow in a relationship with Christ, you must start from accepting Christ and walking in Christ, and continue with being stronger in Christ with indicators of being rooted in Christ, being built on Christ, being growth in faith in Christ and a heart that always grateful.